Nursing perceptions of the preparation of intravenous medicines in paediatric intensive care. Issue 6 (1st February 2011) - Hughes, L; Johnstone, M; Sutherland, A
Abstract : Objective: To evaluate and compare nursing perceptions around intravenous preparation with the reality of intravenous preparation in a 24-bedded Paediatric Critical Care Unit. To assess the attitudes of nursing staff towards pharmacy staff potentially getting involved in intravenous preparation in the near-patient area. To identify those intravenous preparations that nursing staff would prioritise for pharmacy preparation and compare these with a risk-assessment based prioritisation. Methods: Anonymised questionnaires and direct observation of 150 intravenous preparations on the ward. Results: Questionnaire response rate: 33% (130 distributed, 45 returned). Nursing staff have no strong opinion on the preparation of intravenous medicines in the ward environment (mean 4.6/10, median 5.5) which indicates broad acceptance of the role as part of the job, but would suggest a willingness to accept additional support. The majority of nurses estimated each intravenous preparation to be around 5 min (37/44) when in reality it takes an average of 18.9 min to prepare one intravenous dose (range: 5–55 min, median: 15 min). Nursing staff suggest that they would like pharmacy staff to prepare reconstituted antibiotics (18/45) and continuous infusions (20/45) A risk assessment of intravenous drugs on Paediatric Intensive Care Unit (PICU) would lead pharmacy to prioritise continuously infused medicines (eg, inotropes). Conclusion: Nursing staff underestimate how much time is spent preparing intravenous medicines. They acknowledge that there are risks inherent in such processes in a modern PICU. They would accept pharmacy support in ▶ preparation of intravenous doses ▶ training nurses for intravenous preparation.